Designing the editorial experience : a primer for print, Web, and mobile - Apfelbaum, Sue.; Cezzar, Juliette (Beverly, MA : Rockport Publishers, 2014)
"In a world of media that seems to be ever-changing, how do we define a newspaper, magazine or journal? Are we drinking our morning coffee on a Sunday as we sit down and read our newstablet? Look around any doctor's office waiting room and you will find two people reading the same magazine, one holding the paper version, another on their phone. With so many medium options, designers need to evaluate the best formats to convey an editorial vision. In Designing the Editorial Experience, authors Sue Apfelbaum and Juliette Cezzar will discuss what it means to design for multiple media. It features advice from professionals in both the design and editorial fronts --and digital strategists too-- about what is constant and what is changing in the field. Inside, you will find examples of the best editorial design being produced today. In addition, explore the audiences for content, what forms the content takes, and how workflows are managed. This book provides a primer on the elements of editorial design that result in rich, thoughtful, and rewarding editorial experiences"--
Includes bibliographical references and index.
Keywords: Magazine design; Newspaper layout and typography; Graphic design (Typography); Graphic design (Typography) -- Case studies; Electronic publications -- Design; Web sites -- Design